Development of PPKN based learning modules blended learning on material diversity ethnic group nation and culture - Moh. Farid Nurul Anwar; Wahyu Widodo; Kardiana Metha Rozhana; Veneranda Dian Lestari (Universitas Kanjuruhan Malang, 2023)
The purpose of developing this module is to determine the validity and effectiveness of the module implemented in class IV. This research and development refers to the Borg & Gall model. This learning module goes through a validation process, namely validation by material experts, linguists and design experts. From the results of the last validation, the scores were obtained from material experts 90.5%, linguists 76% and design experts 78.3%. The scores obtained from the teacher and student response questionnaires were 96.6% each. 82.5% and 96.45%. The average value of the small group product trial was 72 and in the large group product trial was 93.5, achieved 100% completeness. Based on the analysis of the data from the results of the data research, it can be concluded that the PPKn learning module based on Blended Learning on ethnic and cultural diversity material is stated to be valid and effective in use.